أثر خصائص لجنة التدقيق في الإفصاح عن رأس المال الفكري: أدلة من فسطين: The Impact of Audit committee characteristics on Intellectual capital disclosure : Empirical evidence from Palestine (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The study aimed to examine the impact of audit committee characteristics on the practices of intellectual capital disclosure in the annual reports of Bank and Insurance companies listed on Palestine Exchange, through performing content analysis of the annual reports for the study sample which totaled thirteen companies, including six banks and seven insurance companies. To achieve the study objectives, the study employed a content analysis approach in order to analyze the content of the intellectual capital disclosure practice, in addition, the study used cross-sectional with longitudinal data for time series for a period of time between 2014-2019. The empirical results indicated that financial expertise and the number of meetings of audit committee members enhance the level of intellectual capital disclosure. However, the independency and size of the audit committee were not associated with intellectual capital disclosure.  Therefore, it is recommended that it is necessary to enhance the audit committee effectiveness by identifying the concept of independence that should be available in the members of the audit committee and emphasizing that there are no self-interests or benefits for its members in order to be able to exercise its role effectively, and this is taken into account through the Palestinian Monetary Authority setting clear and specific conditions for independence and what It involves the requirements.